PENGARUH GREEN MARKETING TERHADAP BRAND IMAGE DAN LOYALITAS KONSUMEN (STUDI KASUS PADA PELANGGAN THE BODY SHOP MALL SKA PEKANBARU) - Megiannisa "; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study conducted aims to know that influence of Green Marketing on Brand Image and Customers Loyalty on Customers of The Body Shop in Mall Ska Pekanbaru.The study type used an explanatory research with quantitative approach and the samples are 85 respondents who are customers of The Body Shop Mall Ska Pekanbaru. The Method of data used in this research is questionnaires with purposive sampling techinque,while the analysis of the data used is descriptive analysis and path analysis.The results showed that variable of Green Marketing has direct effect on Brand Image variable; Brand Image variable has direct effect on Customers Loyalty variable; Green Marketing variable has direct effect on Customers Loyalty variable; and Green Marketing has indirect efect on Customers Loyalty trough Brand ImageKeywords: The influence. green marketing, brand image, and customer loyalty